Emotive Language in Political News Articles from The Star and The Washington Post - Tengku Abdul Malik, Tengku Danial; Anuar, Nadia (Development in Language Studies, 2023)
Emotive language is a powerful tool in reporting engaging and interesting reading material as it can evoke different emotions. However, the use of emotive language in media discourse varies according to culture and target readers. The variation between the use of this persuasion tool motivates this study to analyse the use of emotive language in two different news portals, The Star (Malaysia) and The Washington Post (the United States of America). This study scrutinised political news articles that were published between July 2022 and July 2023. Collectively, ten (10) online news articles that report on current political issues were selected for this study. This qualitative study utilised content analysis, anchored on Martin and White's Appraisal model (2005), in assessing the selected online news articles. The results revealed that the news articles from The Star encompassed a diverse range of emotive words related to affect, judgement, and appreciation, suggesting a greater emphasis on evaluating and critiquing various aspects of the news. Conversely, the selected online news articles from The Washington Post concentrated on the use of specific aspects of judgement and valuation. The attributing factors of the dissimilarities in the findings can be further dissected by future studies to enrich intercultural understanding. Therefore, the difference in the use of emotive language between these two media giants is notable and underlines the importance of knowledge in emotive language to foster a media-literate society.